Artemisia herba-alba Essential Oil: Chemical Composition, Phytotoxic Activity and Environmental Safety - Beáta Baranová; Daniela Gruľová; Flavio Polito; Vincent Sedlák; Mária Konečná; Marta Mydlárová Blaščáková; Ismail Amri; Vincenzo De Feo; Janka Poráčová (Plants)
Weeds cause a decrease in the quantity and quality of agricultural production and economic damage to producers. The prolonged use of synthetic pesticides causes problems of environmental pollution, the possible alteration of agricultural products and problems for human health. For this reason, the scientific community’s search for products of natural origin, which are biodegradable, safe for human health and can act as valid alternatives to traditional herbicides, is growing. Essential oils can have useful implications in agriculture by acting as effective alternatives to chemical herbicides. In this work, the chemical composition of an EO from Artemisia herba-alba and its herbicidal properties were studied on two weeds (Lolium multiflorum and Trifolium pratense) and two crops (Brassica napus and Hordeum vulgare) and its environmental safety was also assessed using three model organisms: Chaoborus sp., Tubifex tubifex and Eisenia foetida. The principal component of the EO was camphor (26.02%), with α- and β-thujone (9.60 and 8.38%, respectively), 1,8-cineole (8.02%), piperitenone (5.29%) and camphene (4.95%) as the main components. The EO demonstrated variable phytotoxic effects with a dose-dependent manner, inhibiting both the germination and the radical elongation of the tested seeds, and was also found to be environmentally safe for the selected organisms. The results lay the foundation for considering this EO as a potential weed control agent.